A national survey of oncology survivors examining nutrition attitudes, problems and behaviours, and access to dietetic care throughout the cancer journey. (February 2021) - Sullivan, Erin S.; Rice, Niamh; Kingston, Elaine; Kelly, Aoife; Reynolds, John V.; Feighan, Jennifer; Power, Derek G.; Ryan, Aoife M.
Summary: Background: Attitudes of cancer survivors to nutrition and nutrition care have rarely been captured. A better understanding of their needs based on a review of their experiences would give voice to this patient group (which has rarely been captured) and allow for better planning of nutritional care. Aims: To conduct a national survey to determine: (1) survivors' experience in relation to nutrition and diet-related problems, (2) perceived importance of the role of nutrition to cancer survivors, (3) the experience of accessing dietetic support, (4) the sources where survivors get nutrition information, and (5) their use of alternative dietary strategies. Methods: Survivors (any adult ever diagnosed with cancer) who had been diagnosed with or treated for cancer in Ireland within the past 5 years, were asked to complete a 25-item paper-based survey at one of 20 different hospital sites in Ireland. The survey was also hosted online on the websites of major cancer charities. Descriptive statistics were used to examine quantitative data. Results: In total, 1073 valid responses were received (63% female, mean age 57 years (range 18–88)). Breast cancer was the most common (n = 362), followed by colorectal (n = 121). One third of respondents had metastatic disease. Diet-related problems were reported by 45%. Weight loss was experienced by 44% and amongst those, 42% reported they were 'unhappy or worried' by this, while 27% reportedbeing 'delighted/happy' with their weight loss. Muscle loss was noted by 52%, with 20% reporting they had noticed 'a lot' of muscle loss. Nutrition was rated as 'very/extremely' important to cancer care by 89% of respondents, yet 58% reported being asked about dietary issues by their medical team only 'sometimes', 'rarely' or 'never'. Only 39% had been assessed/treated by a registered dietitian (RD) and 74% rated their advice/care as 'very/extremely' helpful. Worryingly, 39% of survivors with involuntary weight loss, and 29% of survivors on a texture modified diet had not received nutritional care from an RD. Overall, 57% of those who did not see an RD said they wanted more dietetic support (access to a helpline/dietitian/additional reliable information). Of concern, 37% of survivors were following or had tried alternative, unproven dietary strategies (e.g. restrictive diets, herbal remedies, juicing or detoxes), and 32% reported avoiding specific foods, e.g. processed meat or dairy. A majority (56%) felt confused by the often conflicting nutrition information available in the media and offered by people around them. Conclusions: While nutrition is considered highly important by cancer survivors and a high proportion experience potentially serious diet-related problems including weight and muscle loss, fewer than half surveyed had access to a dietitian. Over a third had used at least one alternative dietary strategy, and over half felt confused about nutrition. Comprehensive nutritional screening and referral programmes to oncology dietitians need to be implemented in the ambulatory setting in order to identify and facilitate early management of the nutritional concerns of cancer survivors. Highlights: This is a unique national survey of survivor attitudes and experience of nutrition during cancer treatment. Results showed high rates of self-reported weight loss, diet-related problems and notable muscle loss. Only a minority of cancer survivors had access to a registered dietitian. Many survivors reported trying an alternative dietary strategy and food avoidance practices were high. Cancer survivors feel confused by the amount of conflicting nutrition information available in the media.